2017
DOI: 10.1080/23772484.2017.1319735
|View full text |Cite
|
Sign up to set email alerts
|

A case of cerebellar arteriovenous malformation presented with vertigo, hearing loss, and headache

Abstract: We report a 48-year-old man presented with episodic rotatory vertigo accompanied by right hearing loss and headache. He did not have medical history of migraine. His hearing loss was progressive. He showed unilateral (right-sided) absence of cervical and ocular vestibular evoked myogenic potentials (cVEMP and oVEMP) to the right ear stimulation, while his caloric tests were normal on both sides. His signs and symptoms were suggestive of right peripheral vestibular vertigo except for headache. MRI revealed cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In that study, in the cerebellums of 4 patients; 2 patients have hemangioblastoma, 1 patient has a metastatic breast cancer lesions, 1 patient has metastatic renal cell cancer lesions reported. 3 Similar cases in the literature are as follows: Sakurako et al 4 reported unilateral hearing loss and headache in a 48-year-old vertigo patient. In the vertigo tests of the patient, rotatory nystagmus, which may be compatible with peripheral vertigo, was observed, VEMP responses were not obtained on the side with hearing loss, and both ears' caloric tests were normal.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In that study, in the cerebellums of 4 patients; 2 patients have hemangioblastoma, 1 patient has a metastatic breast cancer lesions, 1 patient has metastatic renal cell cancer lesions reported. 3 Similar cases in the literature are as follows: Sakurako et al 4 reported unilateral hearing loss and headache in a 48-year-old vertigo patient. In the vertigo tests of the patient, rotatory nystagmus, which may be compatible with peripheral vertigo, was observed, VEMP responses were not obtained on the side with hearing loss, and both ears' caloric tests were normal.…”
Section: Discussionmentioning
confidence: 54%
“…Sakurako et al 4 reported unilateral hearing loss and headache in a 48-year-old vertigo patient. In the vertigo tests of the patient, rotatory nystagmus, which may be compatible with peripheral vertigo, was observed, VEMP responses were not obtained on the side with hearing loss, and both ears’ caloric tests were normal.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between vertigo and headache has been known for a long time, but it has only been systematically studied in the most recent 20 years. [1][2][3][4] Vestibular migraine (VM) was defined as recurrent vertigo episodes in patients with a history of migraine or other clinical features of migraine by the Headache Classification Committee of the International Headache Society in 2013. 5 VM is a frequent cause of intermittent vertigo and may also cause symptoms such as nausea, vomiting, and motion sensitivity or visual vertigo in patients with severe VM.…”
Section: Introductionmentioning
confidence: 99%